2020
DOI: 10.3390/s20102773
|View full text |Cite
|
Sign up to set email alerts
|

Validity of a Fully-Immersive VR-Based Version of the Box and Blocks Test for Upper Limb Function Assessment in Parkinson’s Disease

Abstract: In recent decades, gaming technology has been accepted as a feasible method for complementing traditional clinical practice, especially in neurorehabilitation; however, the viability of using 3D Virtual Reality (VR) for the assessment of upper limb motor function has not been fully explored. For that purpose, we developed a VR-based version of the Box and Blocks Test (BBT), a clinical test for the assessment of manual dexterity, as an automated alternative to the classical procedure. Our VR-based BBT (VR-BBT) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 52 publications
(33 citation statements)
references
References 33 publications
0
33
0
Order By: Relevance
“…Immersive VR devices are more expensive and may need an adequate training to use [ 41 ], and they also need further development in order to integrate this technology into the clinical neurorehabilitation [ 44 ]. These systems allow ADLs to be practiced in safe virtual scenarios, to optimize motor learning [ 45 ], and even to assess and measure the different motor conditions [ 46 ]. Therefore, VR devices could be a promising tool in clinical settings for the rehabilitation of patients with neurological disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Immersive VR devices are more expensive and may need an adequate training to use [ 41 ], and they also need further development in order to integrate this technology into the clinical neurorehabilitation [ 44 ]. These systems allow ADLs to be practiced in safe virtual scenarios, to optimize motor learning [ 45 ], and even to assess and measure the different motor conditions [ 46 ]. Therefore, VR devices could be a promising tool in clinical settings for the rehabilitation of patients with neurological disorders.…”
Section: Discussionmentioning
confidence: 99%
“…VR systems allow the creation of virtual environments that can be used to practice, under controlled conditions, different activities that could be hazardous in a real-world setting [ 6 ]. Different characteristics such as difficulty, intensity, exposure duration, and feedback can be adjusted to provide personalized experiences [ 7 ]. Furthermore, VR and interactive video gaming are presented as a motivational therapy that could increase patient adherence to treatment [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Significant improvements of strength, fine and gross coordination, dexterity, and speed of movement were shown. The findings on comparable outcomes with the physical world lead to the validation of fully-immersive VR Box and Blocks Test ( 37 ). The authors suggested that virtual BBT could be used as a reliable indicator and may be accepted by clinicians and patients.…”
Section: Discussionmentioning
confidence: 95%